2012
DOI: 10.1111/jcpe.12000
|View full text |Cite
|
Sign up to set email alerts
|

Very low and low birth weight associated with maternal periodontitis

Abstract: Maternal periodontitis was associated with a decrease in mean birth weight, as well as with LBW and VLBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
2
8
0
2
Order By: Relevance
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association demonstrated between maternal periodontal disease and LBW (Table ) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth . Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring .…”
Section: Discussionsupporting
confidence: 88%
“…The association demonstrated between maternal periodontal disease and LBW ( Table 2) corroborates some previous studies showing that maternal periodontal disease promotes adverse pregnancy outcomes, such as LBW and premature birth. 13,[30][31][32] Notwithstanding, other studies have failed to find effects of maternal periodontal disease on birth weights of offspring. 14,33 Ide and Papapanou 6 considered this association modest but significant, because in each study there is a high degree of variability in the evaluation of the populations as well as differences in the way the data are recorded and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown an association between periodontitis during pregnancy and low birth weight (LBW), very low birth weight (VLBW), preeclampsia, and GDM (Corbella et al, 2016;Guimarã es et al, 2012;Ha, Jun, Ko, Paik, & Bae, 2014;Xiong et al, 2009). Guimarã es et al (2012 showed in their crosssectional study of 1,206 postpartum women that "maternal periodontitis was associated with a decrease in mean birth weight, as well as LBW and VLBW" (p. 1024).…”
Section: Periodontitismentioning
confidence: 98%
“…Increased gingival inflammation is well documented during pregnancy (Ehlers et al 2013, Figuero et al 2013, Niederman 2013 while periodontal diseases increase risk for maternal (hypertension and preeclampsia) and fetal complications (low birth weight and pre-term birth) (Marin et al 2005, Guimaraes et al 2012, Pralhad et al 2013, Ha et al 2014, Jacob & Nath 2014, Rao et al 2014. For example, active periodontal inflammation, as determined by bleeding on probing, has been reported to correlate with reductions in fetal femur length, birth weight and birth length ).…”
mentioning
confidence: 99%